Relaxation of silicon non-equilibrium depletion with majority charge carriers in strong electric fields, its mechanisms and ways to damp it - Primachenko, V.E.; Kirillova, S.I.; Chernobay, V.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
This overview deals with original works of authors as well as with works by
native and foreign authors, which are devoted to this or close topics. It is written with
account of the modern state of the problem, to solve which a great amount of successful
work was made by Academician of NAS of Ukraine O.V. Snitko. Considered in this
paper are the essence of the phenomenon of non-equilibrium depletion with majority
charge carriers that takes place in the field effect in silicon and a set of new phenomena
that were revealed by the authors when investigating this effect. Besides, analyzed in
detail are the processes of acceleration inherent to relaxation of the non-equilibrium
depletion in strong electric fields (Es = 3·10³
– 5·10⁵
V/cm) at silicon surface being in
various physical-and-chemical states. It is noted that the Franz-Keldysh or Frenkel
effects for local centers play the main role in acceleration of relaxation with growing Es
at the silicon surface. In this case, an essential role belongs to electron-phonon
interaction of the charge carrier at the local center with continuum phonons around this
center.